2005
DOI: 10.1091/mbc.e04-07-0627
|View full text |Cite
|
Sign up to set email alerts
|

Annexin 2 Promotes the Formation of Lipid Microdomains Required for Calcium-regulated Exocytosis of Dense-Core Vesicles

Abstract: Annexin 2 is a calcium-dependent phospholipid-binding protein that has been implicated in a number of membrane-related events, including regulated exocytosis. In chromaffin cells, we previously reported that catecholamine secretion requires the translocation and formation of the annexin 2 tetramer near the exocytotic sites. Here, to obtain direct evidence for a role of annexin 2 in exocytosis, we modified its expression level in chromaffin cells by using the Semliki Forest virus expression system. Using a real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
151
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 127 publications
(163 citation statements)
references
References 58 publications
10
151
0
2
Order By: Relevance
“…Resting and stimulated PC12 cells were fixed and further processed for immunofluorescence as described (40,41). Stained cells were visualized with a Zeiss confocal microscope LSM 510.…”
Section: Methodsmentioning
confidence: 99%
“…Resting and stimulated PC12 cells were fixed and further processed for immunofluorescence as described (40,41). Stained cells were visualized with a Zeiss confocal microscope LSM 510.…”
Section: Methodsmentioning
confidence: 99%
“…This plasmid allows also the identification of the subpopulation of cells that transiently express the siRNAs through the immunostaining of GH. In transfected PC12 cells, GH is stored in secretory granules and released by exocytosis in response to cell stimulation (14,24). Western blot analysis revealed that transient expression of PLD1 siRNA reduced the level of PLD1 but did not affect the level of actin or GH (Fig.…”
Section: Pa Is Produced At the Plasma Membrane When Exocytosis Ismentioning
confidence: 92%
“…Secretagogue-evoked stimulation triggers its rapid translocation to the plasma membrane (Fig. 6A), where it stabilizes lipid micro-domains required for exocytosis (Chasserot-Golaz et al, 2005). In Tat-expressing PC12 cells, neither ATP (Fig.…”
Section: Tat Inhibits Chromaffin and Pc12 Cell Exocytosismentioning
confidence: 99%